The North American Consortium for the Study of End‐Stage Liver Disease–Acute‐on‐Chronic Liver Failure Score Accurately Predicts Survival: An External Validation Using a National Cohort. Issue 2 (21st January 2020) - Rosenblatt, Russell; Shen, Nicole; Tafesh, Zaid; Cohen‐Mekelburg, Shirley; Crawford, Carl V.; Kumar, Sonal; Lucero, Catherine; Brown, Robert S.; Jesudian, Arun; Fortune, Brett E.
Abstract : Acute‐on‐chronic liver failure (ACLF) carries high short‐term mortality. The North American Consortium for the Study of End‐Stage Liver Disease (NACSELD)–ACLF score, positive if ≥2 organ failures are present, is a bedside tool that predicts short‐term mortality in patients with cirrhosis. However, it was created using major liver referral centers, where a minority of patients with cirrhosis are hospitalized. Therefore, this study used the Nationwide Inpatient Sample, a nationally representative database, from 2005 to 2014 to externally validate the NACSELD‐ACLF score in a cohort of patients with decompensated cirrhosis who were identified by a validated algorithm. Organ failures were identified using diagnosis codes. The primary objective was to evaluate the association between the NACSELD‐ACLF score and inpatient mortality, whereas secondary objectives compared outcomes depending on presence of infection or hospitalization at a transplant center. Multivariate logistic regression was used to compare outcomes, and area under the curve was calculated. There were 1, 523, 478 discharges that were included with 106, 634 (7.0%) having a positive NACSELD‐ACLF score. Patients were a mean 58 years old, and a majority were white men. Infection was present in 33.7% of the sample. Inpatient survival decreased with each organ failure and if infection was present. Patients with the NACSELD‐ACLF score had significantly lower inpatient survival on crude (94% versus 48%; P  < 0.001) and multivariate analysis (odds ratio [OR], 0.08; 95% confidence interval [CI], 0.07‐0.08) and area under the receiver operating characteristic curve 0.77 (95% CI, 0.77‐0.78). Liver transplant centers had clinically similar but significantly better survival at each organ failure, in patients with the NACSELD‐ACLF score, and on multivariate analysis (OR, 1.17; 95% CI, 1.13‐1.22). Using a national cohort, our study validated the NACSELD‐ACLF score as an excellent, simple bedside tool to predict short‐term survival in patients with decompensated cirrhosis.